Origin of Earth's Water: Chondritic Inheritance Plus Nebular Ingassing and Storage of Hydrogen in the Core. Issue 10 (20th October 2018) - Wu, Jun; Desch, Steven J.; Schaefer, Laura; Elkins‐Tanton, Linda T.; Pahlevan, Kaveh; Buseck, Peter R.
Abstract: Recent developments in planet formation theory and measurements of low D/H in deep mantle material support a solar nebula source for some of Earth's hydrogen. Here we present a new model for the origin of Earth's water that considers both chondritic water and nebular ingassing of hydrogen. The largest embryo that formed Earth likely had a magma ocean while the solar nebula persisted and could have ingassed nebular gases. The model considers iron hydrogenation reactions during Earth's core formation as a mechanism for both sequestering hydrogen in the core and simultaneously fractionating hydrogen isotopes. By parameterizing the isotopic fractionation factor and initial bulk D/H ratio of Earth's chondritic material, we explore the combined effects of elemental dissolution and isotopic fractionation of hydrogen in iron. By fitting to the two key constraints (three oceans' worth of water in Earth's mantle and on its surface; and D/H in the bulk silicate Earth close to 150 × 10 −6 ), the model searches for best solutions among 10, 000 different combinations of chondritic and nebular contributions. We find that ingassing of a small amount, typically >0–0.5 oceans of nebular hydrogen, is generally demanded, supplementing seven to eight oceans from chondritic contributions. About 60% of the total hydrogen enters the core, and attendant isotopic fractionation plausibly lowers the core's D/H to 130 × 10 −6 . Crystallized magma ocean material may have D/H ≈ 110 × 10 −6 . These modeling results readily explain the low D/H in core‐mantle boundary material and account for Earth's inventory of solar neon and helium. Plain Language Summary: People have long had curiosity in the origin of Earth's water (equivalently hydrogen). Solar nebula has been given the least attention among existing theories, although it was the predominating reservoir of hydrogen in our early solar system. Here we present a first model for Earth's water origin that quantifies contribution from the solar nebula in addition to that from chondrites, the primary building blocks of Earth. The model considers dissolution of nebular hydrogen into the early Earth's magma oceans and reaction between hydrogen and iron droplets within the magma ocean. Such processes not only delivered countless hydrogen atoms from the mantle to the core but also generated an appreciable difference in hydrogen isotopic composition (2H/1H ratio) between the mantle and core. Fitting the model to current knowledge about Earth's hydrogen produces best combinations of nebular and chondritic contributions to Earth's water. We find that nearly one out of every 100 water molecules on Earth came from the solar nebula. Our planet hides majority of its water inside, with roughly two oceans in the mantle and four to five oceans in the core. These results suggest inevitable formation of water on sufficiently large rocky planets in extrasolar systems. Key Points: Nebular ingassing supplied 1% of Earth's water budget, complementing seven to eight oceans' worth of chondritic contribution Iron hydrogenation in magma oceans sequestered hydrogen and fractionated its isotopes, requiring α < 0.92 to explain the solar contribution Approximately 60% of Earth's hydrogen resides in the core and has low‐D/H ratios ( 130 times 10 ‐6 )